Parents' Experience in Children's Friendship Training Programme for Their Children with Autism Spectrum Disorder: A Qualitative Inquiry - Sing Yee Ong; Samsilah Roslan; Nor Aniza Ahmad; Ahmad Fauzi Mohd Ayub; Lee Ping Chen; Sahar Mohammed Taresh (MDPI AG, 2021)
Background: Children's Friendship Training (CFT) is a parent-assisted intervention programme that introduces children to basic sets of social rules to help them understand social contexts with specific guidance from their parents. It has been reported in several empirical studies that the friendship skills of children with autism spectrum disorder were enhanced after participating in CFT. However, previous studies only focused on the effectiveness of the training without exploring it from the parent's perspective. As such, the objective of this study is to highlight the parents' experience in assisting in the implementation of CFT. Purpose: To explore the parents' experiences with autism spectrum disorder (ASD) in CFT and examine the experiences using the CFT as a theoretical framework. Methodology: In this study, eight parents and their school-aged children with ASD participated in 12 CFT sessions. Upon completing the CFT, the parents participated in a focus group interview. The interview session was video recorded and transcribed with the parents' consent. Thematic analysis was employed in analysing the collected data as outlined in six different phases. Results: The generated data revealed the similarities and differences in parents' experiences in the CFT. The current study has identified four main themes: (1) fear and resistance; (2) awareness, learning, and adjustment; (3) change is hard; and (4) identifying support. Conclusions: The findings highlighted the processes that these parents experienced and encountered while attending the CFT programme, it is important to consider these processes based on how they might impact the effectiveness of the programme. The programme's effectiveness is reliant on the ability to work closely with parents to understand their challenges and explore the type of support they need. This study has analysed the crucial factors that provide an overview of parents' encounters in their participation in CFT.